The Role of Climate Resilience in Developing Water Security: A Field Study on the Water Situation in Iraqi Society - Najla Kamel Salem, Lect. Dr. (lark, 2025)
Securing access to water is a fundamental concept of human security, as water is the source of life. The Iraqi society faces a significant challenge threatening its water security. Therefore, this study aims to explore the concept of climate resilience, understand the social impacts resulting from water insecurity, and highlight the role that climate resilience plays in enhancing water security, according to strategies adopted by governmental bodies. The researcher employed a social survey methodology using purposive sampling, with a sample size of 30 specialists from the Ministry of Water Resources. The key findings indicate that the adaptive strategies implemented by governmental agencies play a significant role in shaping water resilience. Furthermore, networking and cooperation across all sectors, alongside the activation of local community roles, provide individuals with high resilience in strengthening water security within Iraqi society.
Keywords: climate flexibility , development , water security